Transgenic Introduction of a Glycolate Oxidative Cycle into A. thaliana Chloroplasts Leads to Growth Improvement - Maier, Alexandra; Fahnenstich, Holger; Von Caemmerer, Susanne; Engqvist, Martin K.; Weber, Andreas P.; Flügge, Ulf-Ingo; Maurino, Veronica G. (Frontiers in Plant Science, 2012)
The photorespiratory pathway helps illuminated C3-plants under conditions of limited CO2 availability by effectively exporting reducing equivalents in form of glycolate out of the chloroplast and regenerating glycerate-3-P as substrate for RubisCO. On the other hand, this pathway is considered as probably futile because previously assimilated CO2 is released in mitochondria. Consequently, a lot of effort has been made to reduce this CO2 loss either by reducing fluxes via engineering RubisCO or circumventing mitochondrial CO2 release by the introduction of new enzyme activities. Here we present an approach following the latter route, introducing a complete glycolate catabolic cycle in chloroplasts of Arabidopsis thaliana comprising glycolate oxidase (GO), malate synthase (MS), and catalase (CAT). Results from plants bearing both GO and MS activities have already been reported (Fahnenstich et al., 2008). This previous work showed that the H2O2 produced by GO had strongly negative effects. These effects can be prevented by introducing a plastidial catalase activity, as reported here. Transgenic lines bearing all three transgenic enzyme activities were identified and some with higher CAT activity showed higher dry weight, higher photosynthetic rates, and changes in glycine/serine ratio compared to the wild type. This indicates that the fine-tuning of transgenic enzyme activities in the chloroplasts seems crucial and strongly suggests that the approach is valid and that it is possible to improve the growth of A. thaliana by introducing a synthetic glycolate oxidative cycle into chloroplasts.